EP 47. Direct assessment of psychosocial measures using Eye Tracking Technology in advanced ALS – Can preserved autonomy and psychological wellbeing modify disease course?. Issue 9 (September 2016) - Linse, K.; Rüger, W.; Joos, M.; Schmitz-Peiffer, H.; Storch, A.; Hermann, A.
Abstract : Background: Amyotrophic lateral sclerosis is a terminal motor neuron disease, with progressive paralysis, dysarthria, dysphagia and respiratory disabilities. Eye Tracking based computer systems (ETCS) facilitate communication and participation in advanced quadriplegic and anarthric disease state. The impact of ALS on patients and caregivers wellbeing is controversial, with patients showing surprisingly preserved psychological functioning in some studies. Quality of Life, depression and the impact of communicative functioning, especially ETCS usage in the advanced, quadriplegic disease state has not yet been investigated in a direct, fully independent manner, using ETCS technology. Methods: ETCS-based versions of widely used psychosocial questionnaires (ACSA, ADI-12, SeiQoL-DW, WHO-5) as well as a new questionnaire on communicative functioning were developed. 30 ALS-patients in an advanced disease state were screened, of whom 11 could complete study procedures (ALS-FRS-R: 5.3 ± 5.9; ALS duration: 6.5 ± 3.8 years, range 1–12; 82% invasively ventilated; 82% PEG), including an ETCS-based semi structured interview on sociodemographic data, care conditions, illness parameters, usage and perceived usefulness of ETCS and psychosocial questionnaires. Additionally, 9 family and 10 professional caregivers could be assessed with the same instruments. Results: An eye tracking-based version of the TMT showed good cognitive functioning and high eye tracking accuracy for the assessed patients, ETCS-based completion of interview and questionnaires was feasible. On average patients used the ETCS for 22.3 months (range 1–74) with a mean usage of 9.1 h per day (range 0.5–16), and rated it as highly usable and indispensable. More intensive use was associated with longer disease duration and higher psychological wellbeing. Patients reported high communicative abilities, comparable to caregivers, while their supposition without the ETCS was significantly worse. Depression rates were moderate and comparable for patients and family caregivers (ADI-12: 19.7 ± 5.4 vs. 19.2 ± 6.0, p = .824; WHO-5: 63.6 ± 33.4 vs. 63.8 ± 19.5, p = .766). Patients scored higher in the SeiQoL-DW than their family caregivers (81.3 ± 4.8 vs. 62.8 ± 19.5; p = .020) and higher than their caregivers rated for them (54.2 ± 29.6; p = .027), nominating mainly social activities as important areas of life. Conclusions: Direct assessment of psychosocial measures using ETCS is feasible in the advanced disease state of ALS. Even highly impacted patients with long disease duration can show moderate to good psychological wellbeing, with a potentially high impact of ETCS, enabling communication, social participation and psychological autonomy. Longitudinal investigations are needed. Acknowledgement: The work was supported in part by the Roland Ernst Stiftung Sachsen to A.H. and by a BMBF Grant (16SV5843) to A.H. and M.J.